Fife Cares. (1st March 2011) - Spacey, P; Pairman, S; McCall, M
Abstract : 'Fife Cares' is an integral part of Fife Community Safety Partnerships work to improve the safety of vulnerable residents and deliver the community safety outcome Fewer injuries and losses of life at home and on the roads. Through home visits, the service addresses specific needs and provides tailored advice and assistance. Each visit involves a room by room check for hazards. Electrical sockets, flexes and domestic appliances are checked and minor repairs carried out. Households with no working smoke alarms, are offered the free installation of 10-year battery operated smoke alarms. Advisers undertake a needs assessment, allowing clients to benefit from follow-up visits from partner agencies. Service benefits are measured using a range of outcome measures, number of people visited and feedback from clients and partner services. Figures from NHS Fife indicate the number of emergency hospital admissions involving children aged 16 and under following a home accident declined by 33% between 2001 and 2007. Between 2002 and 2008 admissions involving older people aged 60+ declined by 4%. The numbers of primary fires, have decreased by 31% over the last 5 years with a decrease of 12% from last year. Feedback from partner agencies suggests the service is both effective and valued. Client feedback shows the service promotes peace of mind - helping them to feel safer and more secure in their own homes. Fife Cares is leading nationally, providing an effective model for addressing the safety concerns of vulnerable groups in a cost-effective and targeted way.